2009
DOI: 10.1117/12.2208043
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning in photonics technology education: assessing student learning

Abstract: Problem-based learning (PBL) is an instructional approach whereby students learn course content by collaboratively solving complex real-world problems and reflecting on their experience. Research shows that PBL improves student knowledge and retention, motivation, problem-solving skills, and the ability to skillfully apply knowledge in new situations. One of the challenges with PBL, however, is that real-world problems are typically open-ended with more than one possible solution, which poses a challenge to ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…PHOTON PBL created eight multimedia interdisciplinary Challenges in optics/photonics in collaboration with industry and research universities. The Challenges have been described in detail elsewhere; 3,4 what follows is a brief summary.…”
Section: Photon Pbl Challengesmentioning
confidence: 99%
“…PHOTON PBL created eight multimedia interdisciplinary Challenges in optics/photonics in collaboration with industry and research universities. The Challenges have been described in detail elsewhere; 3,4 what follows is a brief summary.…”
Section: Photon Pbl Challengesmentioning
confidence: 99%
“…An alternative explanation may be that because the TEE students had only completed three STEM PBL Challenges, they had not completely internalized the PBL process. In a previous study 22 , researchers found that engineering technology students who had completed four or more PBL Challenges showed a greater increase in intrinsic motivation as measured by the MSLQ than students who had completed just two, and had a decrease in external motivation, suggesting that over time and with more experience, external motivation could be internalized, resulting in a transition from a goal orientation to a mastery orientation.…”
Section: Resultsmentioning
confidence: 94%
“…Overall, these results suggest that students were more confident in their ability to solve realworld problems as a result of completing the STEM PBL Challenges. As with motivation, prior research 22 shows students who had completed four or more PBL Challenges showed higher levels of self-efficacy as measured by the MSLQ than students who had completed fewer than four PBL challenges, suggesting that students' confidence in their ability to engage in real-world problem solving improves with PBL experience. The small improvement in self-efficacy may also be attributed to the constructivist nature of the PBL learning environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Many of the activities introduced in the Energy Academy relied on aspects of this pedagogy to engage students in design, tinkering, and creation of a product reflecting their collected knowledge or resolution of a particular challenge. Various degrees of constraints or scaffolding were provided until the final project, which was entirely selected and executed by the participants with faculty support for supplying information or training as required.…”
Section: Problem-based Learningmentioning
confidence: 99%